Afatinib as second-line treatment in patients with recurrent/metastatic squamous cell carcinoma of the head and neck: Subgroup analyses of treatment adherence, safety and mode of afatinib administration in the LUX-Head and Neck 1 trial. (October 2019) - Haddad, Robert; Guigay, Joel; Keilholz, Ulrich; Clement, Paul M.; Fayette, Jérôme; de Souza Viana, Luciano; Rolland, Frédéric; Cupissol, Didier; Geoffrois, Lionnel; Kornek, Gabriela; Licitra, Lisa; Melichar, Bohuslav; et al.
Graphical abstract: Highlights: Across all subgroups, a high proportion of patients took ≥80% of assigned afatinib. Safety findings for afatinib were similar across all patient subgroups assessed. Dose reduction of afatinib to <40 mg reduced the incidence and severity of key AEs. PFS with afatinib was similar between oral and feeding tube administration groups. AEs with afatinib were similar between oral and feeding tube administration groups. Abstract: Objectives: Patients with head and neck squamous cell carcinoma (HNSCC) can experience severe symptom burden and/or difficulty swallowing, leading to problems with treatment adherence/administration. In LUX-Head and Neck 1 (LH&N1; NCT01345682), second-line afatinib improved progression-free survival (PFS) versus methotrexate in patients with recurrent/metastatic HNSCC. We report adherence and safety across pre-specified and additional subgroups potentially linked to afatinib PFS benefit in LH&N1 (p16 status, smoking history), and afatinib adherence, safety and efficacy by administration (oral versus feeding tube; post-hoc analysis). Methods: Patients were randomized (2:1) to afatinib (40 mg/day) or intravenous methotrexate (40 mg/m 2 /week). Results: Among 320 afatinib-treated and 160 methotrexate-treated patients, 83–92% and 76–92% (of patients with data available) across all subgroups took ≥80% of treatment. Across p16 status and smoking history subgroups, the most common treatment-related adverse events (AEs) were diarrhea (70–91%), rash/acne (72–84%), stomatitis (34–73%) with afatinib; and included stomatitis (39–100%), fatigue (22–50%), nausea (19–36%) with methotrexate. Dose reduction decreased AE incidence/severity. Baseline characteristics were generally similar between oral/feeding tube (n = 276/n = 46) groups. 89%/89% (of patients with data available) took ≥80% of assigned afatinib. Median PFS was 2.6 versus 2.7 months (hazard ratio: 0.997; 95% confidence interval: 0.72–1.38). The most common afatinib-related AEs were: rash/acne (74% versus 74%), diarrhea (73% versus 65%), stomatitis (40% versus 30%). Conclusion: Subgroup analyses of LH&N1 demonstrate that afatinib has predictable and manageable safety across patient subgroups, with high treatment adherence, and is effective via oral and feeding tube administration.